SIMBOLISME LAUT PADA KISAH MUSA DALAM AL-QURAN DAN TANAKH: TEORI INTERTEKSTUAL JULIA KRISTEVA - Tubagus, Muhamad Tubagus Soleh Tammimi (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
The sea is not just a geographical landscape in the holy books, but a theological symbol that is full of meaning. The sea is a manifestation of its spiritual and existential form, as reflected in two great religious holy books, namely the Qur'an and the Tanakh. In the Qur'an, it is explained not without cause and effect, but there are several messages that make humans use their thoughts to reflect on the greatness of God. Therefore, this study attempts to examine the sea in the story of the prophet Moses not only in terms of ecology but also as a form of theological symbol based on the perspective of the two religious holy books. In addition, it is based on the fact that the sea in the story of the prophet Moses is not merely an understanding of a physical entity, but in it has a more multidimensional and complex meaning in human life. In this paper, the author uses an approach comparing the texts of the Qur'an and the Tanakh using Julia Kristeva's theory with the theory of intertextuality. In both holy books, the sea presents itself as a blessing and destruction of the source of the narrative history of the previous people. Although in its explanation in the Tanakh it is explained explicitly and explained universally in the Qur'an, the symbolic meaning can be analyzed through Julia Kristeva's intertextuality theory, namely parallel. Therefore, this principle actually forms the meaning of the interrelated relationship between humans, God, and nature.